Relationship between the hip joint capsule and piriformis tendon in a simulation of the modified Watson‐Jones anterolateral approach in THA cadaver study. Issue 5 (29th March 2012) - Sasaki, M.; Nagoya, S.; Kaya, M.; Okazaki, S.; Tateda, K.; Kosukegawa, I.; Yamashita, T.
<x xml:space="preserve">Abstract</x> Fifteen fresh frozen cadavers were used for a simulation of the modified Watson‐Jones anterolateral approach in an anatomical study. Several parameters were measured to evaluate the relation between the piriformis tendon insertion and hip joint capsule insertion. The anteroposterior diameter of the piriformis tendon was found to be greater than the medial–lateral diameter, and that the posterior part of the incised hip joint capsule is distant from the piriformis tendon as the piriformis is inserted into the extra‐articular portion. We also found that it was important not to dissect the anteroproximal portion of the greater trochanter to prevent rupture of the piriformis tendon, whereas the posterior portion was relatively safe. Clin. Anat. 26:610–613, 2013. © 2012 Wiley Periodicals, Inc.